Ontogenetic changes to bone microstructure in an archaeologically derived sample of human ribs. Issue 3 (15th November 2019) - Beresheim, Amy C.; Pfeiffer, Susan; Grynpas, Marc
Abstract: There is considerable variation in the gross morphology and tissue properties among the bones of human infants, children, adolescents, and adults. Using 18 known‐age individuals ( n female = 8, n male = 9, n unknown = 1; birth to 21 years old), from a well‐documented cemetery collection, Spitalfields Christ Church, London, UK, this study explores growth‐related changes in cortical and trabecular bone microstructure. Micro‐CT scans of mid‐shaft middle thoracic ribs are used for quantitative analysis. Results are then compared to previously quantified conventional histomorphometry of the same sample. Total area (Tt.Ar), cortical area (Ct.Ar), cortical thickness (Ct.Th), and the major (Maj.Dm) and minor (Min.Dm) diameters of the rib demonstrate positive correlations with age. Pore density (Po.Dn) increases, but age‐related changes to cortical porosity (Ct.Po) appear to be non‐linear. Trabecular thickness (Tb.th) and trabecular separation (Tb.Sp) increase with age, whereas trabecular bone pattern factor (Tb.Pf), structural model index (SMI), and connectivity density (Conn.D) decrease with age. Sex‐based differences were not identified for any of the variables included in this study. Some samples display clear evidence of diagenetic alteration without corresponding changes in radiopacity, which compromises the reliability of bone mineral density (BMD) data in the study of past populations. Cortical porosity data are not correlated with two‐dimensional measures of osteon population density (OPD). This suggests that unfilled resorption spaces contribute more significantly to cortical porosity than do the Haversian canals of secondary osteons. Continued research using complementary imaging techniques and a wide array of histological variables will increase our understanding of age‐ and sex‐specific ontogenetic patterns within and among human populations. Abstract : This study represents an analysis of growth‐related microstructural variation in the rib, employing a micro‐CT approach that provides a diverse array of outcome variables. The use of a non‐weight‐bearing bone allows us to investigate systemic changes, which may be distinct from those more strongly linked to mechanical loading and locomotor maturation. From birth to adulthood, the spongiosa is remodeled into thicker, more dispersed trabeculae as bone size and cortical bone mass increase.